2014
DOI: 10.3109/10409238.2014.925421
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the ClpP serine protease: A model for self-compartmentalized proteases

Abstract: ClpP is a highly conserved serine protease present in most bacterial species and in the mitochondria of mammalian cells. It forms a cylindrical tetradecameric complex arranged into two stacked heptamers. The two heptameric rings of ClpP enclose a roughly spherical proteolytic chamber of about 51 Å in diameter with 14 Ser-His-Asp proteolytic active sites. ClpP typically forms complexes with unfoldase chaperones of the AAA+ superfamily. Chaperones dock on one or both ends of the ClpP double ring cylindrical stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 47 publications
3
73
0
2
Order By: Relevance
“…Inter-ring allostery is a well-established phenomenon in ClpP; for example, in the bacterial ClpAP system, ClpA binding to one ClpP ring also activates the protease activity of the distal ClpP ring through in large conformational changes Liu et al, 2014). Furthermore, various small molecules (e.g., ADEPs) have recently been identified that activate the ClpP complex by conformational changes to the ring structure visualized by cryoEM and single particle averaging (Alexopoulos et al, 2012;Liu et al, 2014). In the second, less favored model ( Figure 6B), ClpT binds primarily to the ClpP ring, while the MYFF loop binds a hydrophobic pocket on the ClpR ring, directly stabilizing the ClpP-ClpR interaction.…”
Section: Clpt1 and Clpt2 Affect Clppr Protease Capacitymentioning
confidence: 99%
“…Inter-ring allostery is a well-established phenomenon in ClpP; for example, in the bacterial ClpAP system, ClpA binding to one ClpP ring also activates the protease activity of the distal ClpP ring through in large conformational changes Liu et al, 2014). Furthermore, various small molecules (e.g., ADEPs) have recently been identified that activate the ClpP complex by conformational changes to the ring structure visualized by cryoEM and single particle averaging (Alexopoulos et al, 2012;Liu et al, 2014). In the second, less favored model ( Figure 6B), ClpT binds primarily to the ClpP ring, while the MYFF loop binds a hydrophobic pocket on the ClpR ring, directly stabilizing the ClpP-ClpR interaction.…”
Section: Clpt1 and Clpt2 Affect Clppr Protease Capacitymentioning
confidence: 99%
“…The Clp system is found in nonphotosynthetic and photosynthetic prokaryotes and in mitochondria and/or plastids in all studied eukaryotes (Sauer and Baker, 2011;Battesti and Gottesman, 2013;Liu et al, 2014;Nishimura and van Wijk, 2015). Throughout evolution, a highly interesting diversification of Clp chaperones, protease core composition, and oligomeric state, as well as adaptors and antiadaptors has occurred, in part to accommodate the vast range of (sub)cellular proteomes, life cycles, and environments.…”
Section: Clpf: a Novel Clp Protease Adaptor With A Unique Tripartite mentioning
confidence: 99%
“…Macromolecular proteolytic machineries, such as the Clp proteases and the 26S proteasome, play a pivotal role in proteostasis. ATP-dependent Clp proteases are present in bacteria and eukaryotic organelles of bacterial origin, namely, mitochondria and plastids, where they regulate a broad range of substrates (Sauer and Baker, 2011;Alexopoulos et al, 2012;Liu et al, 2014;Nishimura and van Wijk, 2015). Clp proteases consist of ATP-dependent chaperones that form hexameric rings, i.e., AAA+ (ATPases associated with diverse cellular activities) chaperones, which associate with a barrel-shaped tetradecameric protease core complex.…”
Section: Introductionmentioning
confidence: 99%
“…An explanation for the unusual ADEP-induced activation in line with all previous experiments would be a stimulation of ClpP through conformational restriction of the complex into a more active form. The ClpP protease is known to be highly dynamic 20 and structural information on SaClpP is available for an active extended 19 , an inactive compact 33 and an inactive compressed 6 conformation 34 . These conformations differ in the height of the barrel (B10 nm for the extended and B9 nm for the compact and compressed conformations), in the alignment of the catalytic triad residues and in the orientation of the E-helix in the handle region ( Fig.…”
Section: Saclpp+u1 (%)mentioning
confidence: 99%
“…In this complex, ClpX engages substrate proteins prone to degradation, unfolds them and threads them into the ClpP proteolytic chamber where they are subsequently degraded [16][17][18] . Crystal structures of the ClpP barrel in different conformations have been solved, including an active extended and an inactive compressed conformation, however, how the associated structural dynamics are regulated is currently not known 6,13,19,20 . ClpP alone is able to cleave only small peptides, with binding of ClpX being strictly required for the degradation of proteins 21 .…”
mentioning
confidence: 99%